Consecutive non-training days over a weekend for assessing cardiac parasympathetic variation in response to accumulated exercise stress. Issue 8 (13th September 2020) - Perrotta, Andrew S.; Koehle, Michael S.; White, Matthew D.; Taunton, Jack E.; Warburton, Darren E.R.
ABSTRACT: Purpose: To examine the association between day-to-day resting cardiac parasympathetic variability over consecutive non-training days (i.e. weekend) and accumulated exercise stress when quantified using indices of cardiovascular strain. Methods: Twelve international calibre female field hockey players training as part of a national team were participants over a four-week mesocycle prior to a 2016 Olympic qualifying tournament. On-field exercise stress was examined using heart rate (HR) dynamics and quantified as; (1) training load and (2) time (min) spent above anaerobic threshold. The square root of the mean squared differences of successive cardiac cycles (R–R intervals) recorded on Saturday and Sunday were individually calculated and log-transformed prior to being averaged (Ln rMSSDweekend). Day-to-day variation in Ln rMSSD over the weekend was expressed using the coefficient of variation (Ln rMSSDCV ). Non-linear regression analysis examined the association between accumulated exercise stress and Ln rMSSDCV . Results: A quadratic association between each index of exercise stress and Ln rMSSDCV was identified. After converting the coefficient of determination into a correlation coefficient (90% CL), the respective association between Ln rMSSDCV and training load (AU); r  = 0.40 (0.16:0.59) and time above threshold; r  = 0.35 (0.06:0.59) were observed. Conclusion: Ln rMSSDCV derived over consecutive non-training days displayed a moderate, yet significant association between accumulated exercise stress when expressed as global or high-intensity indices of cardiovascular strain. Weekend assessments may offer a practical and appropriate juncture between microcycles to assess the magnitude of perturbation in cardiac autonomic homeostasis prior to entering subsequent training periods.